A conceptualisation of narratives and its expression in the CRM. (2017) - Bartalesi, Valentina; Meghini, Carlo; Metilli, Daniele
Current Digital Libraries (DLs) are mostly built around large collections of scarcely related objects. We aim at enriching the information space of DLs by introducing narratives, consisting of two main components: networks of events related to one another and to the DL resources through semantic links, and narrations of those events in texts. In order to introduce narratives in DLs, we developed a conceptualisation based on narratology and we expressed it using the CIDOC CRM and CRMinf as reference ontologies. We used this expression to validate our conceptualisation, creating a narrative of the biography of Dante Alighieri as a realistic case study. To support this experiment, we developed a semi-automated tool that collects basic knowledge about objects and events from Wikidata. The developed ontology is general enough to be not limited to create biographies but other types of narratives as well.